2020
DOI: 10.1016/j.renene.2020.06.101
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a residential heating system using borehole heat exchanger coupled with solar assisted PV/T heat pump

Abstract: Borehole heat exchanger (BHE) is a promising method for extracting heat from the deep geothermal energy which has been widely used for residential heating in high latitude areas. The solar assisted photovoltaic/thermal (PV/T) heat pump could convert solar energy into useful heat efficiently, and could be further used to heat water from the BHE to a higher temperature level. In this paper, a residential heating system using BHE coupled with solar assisted PV/T heat pump is therefore proposed with further perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The system's electrical efficiency was 9%, and the COP reached up to 3.1 while providing hot water up to 40 • C. The energy performance of four system configurations shown in Figure 11 for space heating and domestic hot water in a single-family house is compared in [80] using results from TRNSYS and reported that the simpler configuration involving PVT and heat pump is a good solution for heatingdominated buildings. Yao et al [81] have proposed a hybrid residential heating system using a direct expansion solar PVT assisted heat pump with a borehole heat exchanger (BHE). The authors compared the performance of the hybrid system with a single BHE and reported that the former had better thermal energy performance.…”
Section: Water-based Pvt Systemsmentioning
confidence: 99%
“…The system's electrical efficiency was 9%, and the COP reached up to 3.1 while providing hot water up to 40 • C. The energy performance of four system configurations shown in Figure 11 for space heating and domestic hot water in a single-family house is compared in [80] using results from TRNSYS and reported that the simpler configuration involving PVT and heat pump is a good solution for heatingdominated buildings. Yao et al [81] have proposed a hybrid residential heating system using a direct expansion solar PVT assisted heat pump with a borehole heat exchanger (BHE). The authors compared the performance of the hybrid system with a single BHE and reported that the former had better thermal energy performance.…”
Section: Water-based Pvt Systemsmentioning
confidence: 99%
“…As over 50% of the total cost of the geothermal project can be drilling costs [69], a good solution to reduce high drilling costs is presented by using depleted and abandoned gas and oil wells, which has been extensively investigated recently [70][71][72][73]. Depending on the obtained temperature in DBHE, these systems can be used for direct space heating [74,75], coupled with heat pumps [76][77][78], or even in power production systems [79].…”
Section: Vertical Heat Exchanger Configurationsmentioning
confidence: 99%
“…This would improve the coefficient of performance (COP) of the heat pump and reduce the losses from the district heating network. A study carried out showed that a heat pump integrated with a solar thermal collector could have a solar fraction of up to 67.5% [56]. In addition, the solar energy could be utilized throughout the year by storing excess heat energy in the seasonal storage to be used during winters, when no solar energy is available in Nordic countries.…”
Section: Introductionmentioning
confidence: 99%